Pengaruh Perceived Ease of Use, Enjoyment dan Trust Terhadap Repurchase Intention dengan Customer Satisfaction Sebagai Intervening pada Belanja Online (Studi Pada Mahasiswa Universitas Tanjungpura Pontianak) - Juniwati, Juniwati (Fakultas Ekonomi dan Bisnis, UNTAN, 2015)
This study aims to determine the influence of perceived ease of use, perceived enjoyment, and trust on customer satisfaction and repurchase intention in online shopping of apparel. The design of the study is a survey research with type of research is explanatory, sample used of 100 people. The data analysis technique used is path analysis. The results showed that perceived ease of use variable has no significant influence on customer satisfaction, while perceived enjoyment and trusts have positive and significant influence on customer satisfaction. The results also showed that perceived enjoyment and customer satisfaction has no significant influence on repurchase intention, while perceived ease of use and trust has positive and significant influence on repurchase intention.